Chemical, microbial and sensory properties of a chestnut and milk ice cream with improved healthy characteristics - Luis A. Espinoza; Laura Purriños; Juan A. Centeno; Javier Carballo (International Journal of Food Properties, 2020)
With the aim of revalorization of two productions of economic relevance (milk and chestnuts), a novel ice cream was formulated incorporating milk, chestnut flour and chestnut bits. Using the best sensory valued formula as a basis, eight ice cream formulations were elaborated replacing the ingredients normally used (milk fat, sucrose and carboxymethylcellulose) by healthier ones (olive oil, erythritol + steviol glycosides, and tara (Caesalpinia spinosa) gum, respectively). The formulations were analyzed for composition, physicochemical parameters, fatty acid profile, volatile profile, microbiological characteristics and sensory attributes. A general preference of the tasters was observed for the formulations containing sucrose over those made with the hypocaloric sweetener.